Functional redundancy of Amazonian dung beetles confers community-level resistance to primary forest disturbance - Nunes, Cássio Alencar (2021)
Tropical forest biodiversity is being threatened by human activities, and species losses during forest disturbance can compromise important ecosystem functions and services. We assessed how species losses due to tropical forest disturbance affect community functional structure, using Amazonian dung beetles as a model group. We collected empirical data from 106 forest transects and used simulated extinction scenarios to determine how species loss influences community structure at regional and local scales. Although functional and taxonomic community metrics were largely unaffected by primary forest disturbance, they differed markedly between primary and secondary forests. However, our extinction scenarios demonstrated scale-dependence of species losses, whereby functional structure only eroded with species extinction at the local scale. Hence, we extend the spatial insurance hypothesis by demonstrating that landscape-scale functional redundancy offsets the impact of local species losses and confers community-level resistance to primary forest disturbance.